Integrating Public Health and Health Promotion Practice in the Medical Curriculum: A Self-Directed Team-Based Project Approach - Kershaw, Geraldine; Grivna, Michal; Elbarazi, Iffat; AliHassan, Souheila; Aziz, Faisal; Al Dhaheri, Aysha Ibrahim (Frontiers in Public Health, 2017)
Preparing health professionals in Health Promotion (HP) and disease prevention is essential for improvement of population health, community health promotion, and better health care for individuals. The aim of this article is to describe a HP project in the form of a major self-directed project based learning task integrated within the curriculum in the second year of the medical degree program at United Arab Emirates University. The project introduces students to public health and HP practice, and develops students’ literature searching, writing, presentation skills, and team work. Students learn the principles underlying behavioral change, and the design of HP programs and materials, through a lecture format. Small groups of students each choose a specific health topic for their project. Over 11 weeks, students obtain information about their topic from appropriate sources (library, PubMed, Google Scholar, credible health sources such as WHO). Using the principles learned in the lectures, they develop appropriate materials for their target audience: for example, posters, a pamphlet, social media content, or a video or radio message. Students seek advice from specialist faculty as needed. In week 12 each team presents their project background, rationale, and materials to their colleagues in a seminar format open to all faculty. They then submit the materials they developed for assessment. Group marks are assigned for presentations and materials. Key concepts are assessed by multiple choice questions in comprehensive course examinations. By participation in the HP project, many students develop a solid background in prevention. The information retrieval, writing, and presentation skills, as well as experience of team work, are valuable both for the remaining years of their training and their future careers.